Toxin-Antitoxin Systems in Estuarine Synechococcus Strain CB0101 and Their Transcriptomic Responses to Environmental Stressors - Marsan, David; Place, Allen; Fucich, Daniel; Chen, Feng (Frontiers in Microbiology, 2017)
Bacterial toxin-antitoxin (TA) systems are genetic elements composed of a toxin gene and its cognate antitoxin, with the ability to regulate growth. TA systems have not previously been reported in marine Synechococcus or Prochlorococcus. Here we report the finding of seven TA system pairs (Type II) in the estuarine Synechococcus CB0101, and their responses of these TA genes to under different stress conditions, which include; nitrogen and phosphate starvation, phage infection, zinc toxicity, and photo-oxidation. Database searches discovered that 8 other marine Synechococcus strains also contain at least one TA pair but none were found in Prochlorococcus. We demonstrate that the relB/relE TA pair was active and resulted in RNA degradation when CB0101 was under oxidative stress caused by either zinc toxicity or high light intensities, but the growth inhibition was released when the stress was removed. Having TA systems allows Synechococcus CB0101 to adapt to the low light and highly variable environments in the Chesapeake Bay. We propose that TA systems could be more important for picocyanobacteria living in the freshwater and estuarine environments compared to those living in the open ocean.